New directions in strategic thinking 2.0 : ANU Strategic & Defence Studies Centre's golden anniversary conference proceedings - Glenn, Russell W. (ANU Press, 2018)
July 1966 saw the founding of The Australian National University's Strategic & Defence Studies Centre (SDSC). Fifty years later, the Centre celebrated its half-century of research, publication, teaching and informing government decision-makers with a two-day conference entitled 'New Directions in Strategic Thinking 2.0', the numerical designator being a tip of the hat to a similar event conducted, as noted in Dr Brendan Taylor's foreword, in 1980. That pair of days saw the podium graced by many of the world's premier thinkers in the strategic studies field. The evening between them brought together academics, practitioners and other honoured guests at a commemorative dinner held beneath the widespread wings of the 'G for George' bomber in the Australian War Memorial, an event privileged by speaker Brendan Sargeant, Associate Secretary of the Australian Department of Defence, and Professor Desmond Ball making one of his last public appearances--Introduction.